Flow and heat transfer characteristics of microchannel with grooves structure on sidewalls - ZHU Qifeng; CUI Yang; ZHAO Tongle; WEN Xiaoping; SUN Haolei; HE Wenqiang (河南理工大学学报. 自然科学版)
ObjectivesIn order to explore the effects of grooves shape on the liquid flow and heat transfer performances in microchannel heat sink（MCHS）， find an optimal groove geometry that can provide an efficient cooling performance with heat transfer enhancement as well as microchannel flow drag reduction，Methodsan experimental study was carried out to test the fluid pressure and temperature at the microchannel inlet and outlet. The flow friction factor， average Nusselt number， enhanced heat transfer factor and field synergy number were used to evaluate the forced convection flow and heat transfer performances of the deionized water in the fan-shaped grooved microchannel， water droplet grooved microchannel and trapezoidal grooved microchannel. Furthermore， a comparison of the flow and heat transfer performances of the grooved microchannel heat sinks with that of the smooth one was promoted.ResultsWith the increase of volume flow rate， the liquid flow pressure dropped， average Nusselt number and enhanced heat transfer factor increased， while the flow friction factor， temperature increment and field synergy number decreased accordingly， indicating that the pump power consumption of the liquid flow in microchannels increasesd， but its convective heat transfer performance and heat transfer efficiency were significantly improved. The liquid flow pressure drop and friction factor of the grooved microchannel are respectively lower than that of the smooth one， promoting a reduction in the pump power consumption. When the liquid flow rate was large， the heat transfer performance and heat transfer efficiency of the water droplet grooved microchannel and trapezoidal grooved microchannel were better than that of the smooth one. The heat transfer performance and heat transfer efficiency of the fan-shaped grooved microchannel were the best and the corresponding average Nusselt number and enhanced heat transfer factor achieved up to 7.81 and 1.32， respectively.ConclusionsThis research results could provide a reference for improving microchannel design to solve the cooling problem of very large scale integrated （VLSI） chips.